Revitalization of the national consciousness of youth (Journal of Philosophy Culture and Political Science, 2023)
Historical experience shows that an integral part of the transformation of the social system is the process of changing group and individual consciousness, determined by objective and subjective factors.Knowledge and understanding of trends in the development of this process involves studying the characteristics and nature of changes in the consciousness of various social groups, identifying dominant values, motives, attitudes, understanding the origins and causes of changes in consciousness, both positive and negative, correlating them with the needs of society. In this regard, our research is aimed at identifying the need to create a holistic socio-philosophical vision of the ongoing processes, which could form a theoretical and methodological basis for making managerial decisions and purposeful regulation of all spheres of human activity.In a modern country, the social structure of society has changed significantly, one social group has been replaced by others, their social status and role have changed, as well as the ratio. The consciousness of these groups has undergone and is undergoing a transformation. In the process of reforming society, intra- and intergroup dynamics are increasing, the boundaries between different groups are blurring, the mobility of individual members of society in an intergroup environment is often expressed in an insufficiently clear group position of an individual. The "massivization" of all spheres of public life, including spiritual life, brings to the fore mass consciousness, the signs of which are: the displacement of rational components by irrational ones, the predominance of emotions and feelings, a decrease in confidence in the future, a decrease in social activity. In these conditions, the tasks of this study become relevant and practically necessary – to analyze the origins of the above processes, identify trends in their development and concretize the scientific categories "mass" and "mass consciousness".In modern society, the state of mass consciousness is determined not only by the deterioration of objective living conditions, but also depends on the destructive informational and psychological impact exerted on it, under which people lose an objective view of events and facts, the ability to distinguish truth from lies decreases, mental anomalies develop that negatively affect people's own lives and their social role in society.The greatest manifestation of these processes is observed in young people. The formation of this group took place in conditions when there was a sharp polarization of various strata of society, not only in terms of living standards, but also in terms of views on life, such as political and ideological orientation, attitude to the goals and meaning of one's own life. Many researchers of youth problems openly admit that there have been significant deformations of youth consciousness (Anderson et all 1996). They were expressed in the "collapse of ideals", a negative attitude to the history and traditions of society, the growth of social nihilism, the desire for "independence" from society, understood as permissiveness. Therefore, today there is an urgent need to study the consciousness of youth as a large social group, as well as taking into account intra-group differentiation, which is the purpose of this study. The scientific and practical significance of this study lies in the fact that the solution of this problem will contribute to the development of scientific foundations for the modification of youth policy in the country.The research applied the methods of reviewing the existing scientific literature on consciousness and its levels, the method of scientific analysis and synthesis of factors affecting the deformation of youth consciousness in modern realities. The results of the study show that modern youth, due to the peculiarities of their age, relatively easily accepts norms, values, patterns of the new, which allows us to hope for the positive development of this social group. The conducted research revealed that the main factor influencing the consciousness of the young society is the mass media; and despite the differences in the choice of mass media, in general, the level of trust in relation to the media is quite high. The author substantiates the need to regulate the activities of the mass media, as well as to develop a program to ensure information and psychological security for both individuals and groups within the framework of a unified youth policy, in which social philosophy should play a significant role. The condition for the implementation of such a program is the implementation of the national security doctrine, which includes the protection of the security of the individual, society and the state.Keywords: renaissance, national consciousness, youth, deformations, philosophy